Miniaturized log-periodic monopole antenna - Sung, Benedict Zong Wei (Nanyang Technological University, 2023)
In this project, a conventional log-periodic monopole antenna is designed, the log-periodic array consists of 10 elements that operate within 4-8GHz. The array was fed by a meandering microstrip transmission line to achieve a 180° phase delay between adjacent monopoles. Top hat was loaded to the design the miniaturize the antenna, both designs were tested using ANSYS HFSS. Similar results of VSWR of less than 2.05 was observed with some peaks in values ranging from 2.6 to 2.8 were obtained for both design. The profile of the antenna was reduced from 0.25λ to 0.153λ.